A REVIEW OF THE INFLUENCE OF ARTIFICIAL INTELLIGENCE IN ACADEMIC WRITING - Subedi, Rameshor; Nyamasvisva, Tadiwa Elisha (Yayasan Nuraini Ibrahim Mandiri, 2024)
have revolutionized many aspects of the writing process, offering both opportunities and challenges for researchers, academicians, students and educators. AI in academic writing presents substantial possibilities by acting as an intelligent writing assistant, language translator, supporting automated summarization, enhancing writing styles and grammar, and enabling data analysis and visualization. To ascertain the influence of AI in academic writing, a comprehensive review of literature related to artificial intelligence, machine learning, and academic writing were conducted. This study aims to address three distinct challenges, including the widespread usage of AI-enabled tools for academic writing, problems with authorship, copyright, and plagiarism in AI-generated content, and how these problems might be fixed. The primary aim of this article is to recognize and highlight the implication of AI in the context of academic writing. To improve their writing abilities, particularly in academic writing, learners, academic researchers, authors, and educators would benefit more from this study. However, the authorship, copyright and plagiarism should be taken into consideration. In the machine generated text, the authorship and copyright go to the user who gives the input in his. When AI-generated text is combined with original content and thoroughly reviewed using plagiarism detection software, it helps reduce the risk of plagiarism. Keywords: Artificial Intelligence, Machine Learning, Academic Writing, Natural Language Processing